Correct Definition of Sound Speed and Its Consequences in the Tasks of Hydrodynamics. (27th October 2016) - Kirtskhalia, Vladimir
Abstract : The paper considers the applied problems of hydrodynamics and based on the new results, published by the author in recent years, shows that main assumptions used in the course of their solution, namely, incompressibility of liquids and potentiality of their movement, are not applicable to liquids in the gravitational field of the Earth.